Conductivity of poly(methyl methacrylate)/polystyrene/carbon black and poly(ethyl methacrylate)/polystyrene/carbon black ternary composite films - Xu, Huagen; Qu, Muchao; Pan, Yamin; Schubert, Dirk W. (Chinese Journal of Polymer Science, 2019)
Both poly(methyl methacrylate) (PMMA)/polystyrene (PS)/carbon black (CB) and poly(ethyl methacrylate) (PEMA)/PS/CB ternary composite films were obtained using solution casting technique to investigate double percolation effect. In both PMMA/PS/CB, PEMA/PS/CB ternary composite films, the CB particles prefer to locate into PS phase based on the results of calculating wetting coefficient, which is also confirmed by SEM images. The conductivity of the films were investigated, the percolation threshold (c) of both ternary composite films with different polymer blend ratio were determined by fitting the McLachlan GEM equation. Conductivity of PMMA/PS/CB ternary composite films shows a typical double percolation effect. However, due to the double emulsion structure of PEMA/PS polymer blends, even the CB only located in PS phase, the PEMA/PS/CB ternary composite films (PEMA/PS = 50/50) shows a higher c, which conflicts with double percolation effect. A schematic diagram combined with SEM images was proposed to explain this phenomeno
Keywords: Double percolation effect; Conductivity; Ternary composite films; Compatibility